Najwięksi zwycięzcy i przegrani w historii giełdy XX–XXI w. - Bartosiewicz, Aleksandra (Przegląd Nauk Historycznych, 2015)
The article presents profiles of chosen stock investors of the 20th and 21st century. Some of them earned a fortune in the stock market and since then have been considered the best investors of all time. Other, on the contrary, lost their reputation and ended brilliant careers in prison. The article briefly describes lives of them and studies factors that contributed to such a great success or spectacu-lar failure in each case.